Risk factors associated with high blood pressure in older adults at El Mate community - Palacios, Gary M.; Cedeño, John W.; Intriago, Pablo A. (Revista Gregoriana de Ciencias de la Salud, 2024)
High blood pressure (HBP) corresponds to one of the main global public health problems according to the Pan American Health Organization, where it has been indicated that it is the main risk factor for suffering from cardiovascular diseases. The objective is to describe the impact of risk factors associated with high blood pressure in older adults in the El Mate community belonging to the Santa Ana canton. For this, an experimental study was carried out, with a sample of 20 people. Data collection was carried out through a structured survey about HBP. As such, it affected older adults between the ages of 65 and 70 by 70%. In addition, other risk factors related to the lack of control routines, lack of awareness, the existence of bad lifestyles, socioeconomic problems and lack of knowledge of the disease.